2015
DOI: 10.1016/j.ijid.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temperature and humidity measures on influenza A (H7N9) outbreaks—evidence from China

Abstract: We provide direct evidence to support the role of climate conditions in the spread of H7N9 and thereby address a critical question fundamental to our understanding of the epidemiology and evolution of H7N9. These findings could be used to inform targeted surveillance and control efforts aimed at reducing the future spread of H7N9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
5
27
1
1
Order By: Relevance
“…Our results can impact the poultry market reducing the number of cases of H7N9, this coincide with Xu et al (2013) and with Yu et al (2014). We coincide with Tsuchihashi et al (2011), Herrick et al (2013), and Zhang et al (2015), because temperature influences the high risk of infection.…”
Section: Totalsusceptiblessupporting
confidence: 89%
See 1 more Smart Citation
“…Our results can impact the poultry market reducing the number of cases of H7N9, this coincide with Xu et al (2013) and with Yu et al (2014). We coincide with Tsuchihashi et al (2011), Herrick et al (2013), and Zhang et al (2015), because temperature influences the high risk of infection.…”
Section: Totalsusceptiblessupporting
confidence: 89%
“…In our paper no significant correlation was found with the relative humidity with the susceptibility, this coincide with Zhang et al (2015) in which the relative humidity do not influence in the appearance of the virus on influenza A (H7N9), the humidity is usually regarded as a factor impacting on the transmission of diseases, that are transmitted by droplets or aerosols according to Koep et al (2013) and Jaakkola et al (2014). Our results can impact the poultry market reducing the number of cases of H7N9, this coincide with Xu et al (2013) and with Yu et al (2014).…”
Section: Totalsusceptiblessupporting
confidence: 62%
“…. In human influenza outbreaks, seasonal patterns of IAV transmission have been associated with climatic and environmental factors, particularly low humidity and low temperatures . Although our data are suggestive of a similar mechanism, additional epidemiologic and experimental studies that determine the relationship between IAV in swine and climatic and environmental conditions such as temperature and humidity are necessary.…”
Section: Discussionmentioning
confidence: 56%
“…In human influenza outbreaks, seasonal patterns of IAV transmission have been associated with climatic and environmental factors, [38][39][40] particularly low humidity and low temperatures. 41,42 Although our data are suggestive of a similar mechanism, additional epidemiologic and experimental studies that determine the relationship between IAV in swine and climatic and environmental conditions such as temperature and humidity are necessary. A five-year active IAV surveillance study in a single production system demonstrated a negative correlation between herd-level IAV prevalence found in one month to the absolute humidity and outdoor air temperature found in the prior 0-3 months.…”
Section: Discussionmentioning
confidence: 65%
“…As for H7N9, both daily minimum and daily maximum temperatures have been reported to contribute significantly to human infection, but not relative humidity [22]. Other meteorological factors have not been reported.…”
Section: Discussionmentioning
confidence: 99%